Pengaruh Return On Asset, Return On Equity, dan Price Earning To Ratio Terhadap Harga Saham Syariah Berasarkan Closing Price Pada Perusahaan yang Terdaftar di Jakarta Islamic Index Periode Tahun 2020-2022 - Miza Gusmina; Sri Deti; Jum’an (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2023)
Investing in the capital market, investors need accurate information, so they are not trapped in adverse conditions. One of the information that can be used by investors in assessing a company is financial statements. For investors, financial statements are useful for determining the best and profitable investment decisions. Based on the analysis of financial statements, investors can find out the comparison of the intrinsic value of the company's shares compared to the market price of the company's shares. To measure stock prices, it can be known from the influence of financial ratios on stock prices. Financial ratios are designed to show the relationship between financial statement estimates. This study aims to determine the effect of Return On Asset, Return On Equity ((ROE), and Price Earning to Ratio on Sharia Stock Prices based on Closing Prices in Companies listed on the Jakarta Islamic Index (JII) for the 2020-2022 period. The research method is quantitative research, technical data analysis using descriptive statistics. The source of research data is secondary data in the form of financial statements and stock prices from companies listed on the Jakarta Islamic Index (JII) for the 2020-2022 period using purposive sampling techniques. Secondary data processing using SPSS analysis technique version 23. Hypothesis testing in this study used multiple linear regression tests. Based on the results of the study shows that Return On Asset partially does not affect Islamic stock prices, Return On Equity partially has a positive and significant effect on Islamic stock prices, and Price Earning to Ratio partially does not affect Islamic stock prices. Return On Asset, Return On Equity, Price Earning to Ratio simultaneously have a positive and significant effect on Islamic stock prices in companies listed on the Jakarta Islamic Index (JII) for the 2020-2022 period.